A needs analysis in improving writing class activities in EFL classroom context - Husain, Desy Liliani; Nggawu, La Ode (ARKA INSTITUTE, 2022)
The study was intended to assess the existing writing activities conducted in 2013 curriculum setting. Specifically, it also identified the students’ needs in writing skill activity in terms of learning difficulties in writing activity, students’ preferred materials and activities, and students’ responses to teacher’s performance in writing activities. It aims to see the gap results in desired result and current performance and finding out the ways to fill the gap. The questionnaire on need analysis was administrated to 20 students of class XI IPA 2 of SMAN 3 Kendari, South East Sulawesi. There are some major findings on the study, they are (1) students need a more detailed explanation about writing process, such as explanation on how to begin a writing, find ideas to be written, organize paragraph in a logical order, evaluate and revise the writing, (2) students need various topics of writing (3) students need more attractive learning activities, such as they can put in individual work, pair work and group work, and the last (4) students need the teacher to provide appropriate feedback on their writing.